Systematic review of Neotropical Lauxaniidae genera: Cephalella Malloch (Diptera, Schizophora) - Silva, Vera Cristina [UNESP] (Sociedade Brasileira de Zoologia, 1999)
Cephalella Malloch, 1926, a monotypic Neotropical Lauxaniidae genus, characterized by the presence of long antennae and a prominently convex face, is reviewed. The range of C. fumipennis is amplied.
Keywords: Cephalella; Diptera; Lauxaniidae; Neotropical Region; systematic